Gas pipeline preferential site selection occurrence for elemental sulphur & other particle matter formation & deposition - Pack, David; Parks, David; Chesnoy, A. (Elsevier BV, 2012)
Field observations of “elemental sulphur” deposits within high-pressure natural gas transmission pipeline systems have prompted investigations into the study of preferential site selection process for the formation and deposition of these sulphur based contaminants. These deposits can cause complete blockage of the gas stream path. There have not been any known studies into why this preferential site selection process exists, and therefore it is the aim of this research to investigate plausible reasons by investigating affected pipeline systems. The results from the studies, which have been validated against known “elemental sulphur” affected transmission pipeline sites, confirm that the flow dynamics at the pipeline “T” junction could be a major contributing factor to the preferential site selection process. The paper discusses the results.